Menumbuhkan Jiwa Kepemimpinan Generasi Muda Melalui Kewirausahaan Di Desa Karunia Kecamatan Palolo Kabupaten Sigi - Juemi Juemi; Daniel T. Todapa (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Community Service Activities are one of the Tri Dharma of Higher Education that must be implemented. This community service activity was held in Karunia Village, PaloloDistrict, Sigi The method used is the mentoring and training approach or the Participatory Learning Process. Canuna Village. So the purpose of this Community Service Activity is to provide material understanding of the importance of the leadership spirit of the younger generation through entrepreneurship. The results of the Community Service mean that community service activities like this are very beneficial for the village community in growing the leadership spirit of the younger generation. Participants in this activity were youth and community leaders. Participants were very enthusiastic about following the material through lectures, questions and answers and discussions, suggestions that can be given to the Village.